Triangulering - En studie av Maersk Lines merchant haulage - Blomstervall, Sebastian; Lövström, Ludwig (My University, 2014)
Maersk Line act in an industry where differentiation towards competition and depressed prices are parts of all actors’ daily challenges. To become more competitive in relation to other actors, new and more efficient solutions for their customers are always welcomed. What can be stated is that many solutions are connected with costs, which leads to investigations on how to minimize such costs. One method of minimizing costs is by triangulating the company’s container flows. This report investigates the solution with triangulation where, instead of handle import and export customers one by one, by doing this, the customers will split the costs evenly between each other instead of paying one whole round trip by themselves. The report examines Maersk Lines merchant haulage transports with the help of quantitative data supplemented by qualitative data collected from interviews with employees at Maersk Line to create a picture of where the cargo that Maersk Line does not transport, goes to be able to use this in the procurements with the subcontractors that performs Maersk Lines carrier haulage The study showed that the insufficient information regarding the flows from a geographical perspective, no matching flows were able to identify for triangulation. This is because the challenges are greater than to only view it from a geographical perspective. Many more aspects need to be considered to be able to make a decision if triangulation is applicable. Further, a lot of the customers with big flows have thereby custom made solutions created by them to suit their organization the best. This makes it even more difficult for Maersk Line to offer more attractive solutions than these customers already have.
Keywords: Annan teknik; Transport; Other Engineering and Technologies; Transport